The definition of precategorial "cendas" in Kamus Dewan fourth edition - Hassan, Noor Roza; Mohd Kiram, Norazlina; Jumaat, Nur Hidayah (Human Resource Management Academic Research Society, 2023)
Precategorial is a word that cannot stand alone without affixes, does not exist in an imperative form and does not have a passive construction. It can exist in the form of a compound word, phrase or kata ganda berentak that carries a related meaning. The formation of its own entry for this type of word is necessary as the problem will be more complicated if the combination of affixes occurs (Baharom, 2009). Hassan (2019) found that there is an overlap of meaning for precategorial in Kelantanese dialect which causes confusion among the users. The importance of this study is to examine the definition of precategorial “cendas” in Kamus Dewan Edisi Keempat. This study was designed with three main objectives which are to identify precategorial "cendas" in Kamus Dewan Edisi Keempat, to explain the definition of precategorial "cendas" based on the Meaning Components Analysis Theory (1975) and to re-evaluate the definition. Therefore, this study only focuses on the precategorial "cendas" which is also an entry in the Kelantanese dialect (KD). This study uses literature research as well as field research involving respondents who are native speakers of the Kelantanese dialect, interviews and audio recordings. The findings show that this study can overcome the confusion faced by the dictionary users with the new form of definition. Therefore, this research which is related to lexicography that crosses the linguistic discipline is necessary in dealing with various problems and confusion among Malay language users.